Filsafat Pancasila Sebagai Basis Pergerakan Mahasiswa, Kehidupan Sosial, dan Spirit Kewirausahaan - Condra Antoni (Politeknik Negeri Batam, 2012)
The article discusses the meaning and implementation of philosophy of Pancasila in nowdays life. As theoritical study, many students get difficulties in understanding philosophy of Pancasila and how it is related to real life. By analyzing the practices of philosopy of Pancasila, it is found that there is a number of relationships between philosophy of Pancasila and the values in student movements as well as social life. Further, it is also related to the spirit of entrepreneurship since it is based on the faith in God Almighty